Flies Avoid Current Atmospheric CO2 Concentrations - Üçpunar, Habibe K.; Grunwald Kadow, Ilona C. (Frontiers in Physiology, 2021)
CO2 differs from most other odors by being ubiquitously present in the air animals inhale. CO2 levels of the atmosphere, however, are subject to change. Depending on the landscape, temperature, and time of the year, CO2 levels can change even on shortest time scales. In addition, since the 18th century the CO2 baseline keeps increasing due to the intensive fossil fuel usage. However, we do not know whether this change is significant for animals, and if yes whether and how animals adapt to this change. Most insect possess olfactory receptors to detect the gaseous molecule, and CO2 is one of the key odorants for insects such as the vinegar fly Drosophila melanogaster to find food sources and to warn con-specifics. So far, CO2 and its sensory system have been studied in the context of rotting fruit and other CO2-emitting sources to investigate flies’ response to significantly elevated levels of CO2. However, it has not been addressed whether flies detect and potentially react to atmospheric levels of CO2. By using behavioral experiments, here we show that flies can detect atmospheric CO2 concentrations and, if given the choice, prefer air with sub-atmospheric levels of the molecule. Blocking the synaptic release from CO2 receptor neurons abolishes this choice. Based on electrophysiological recordings, we hypothesize that CO2 receptors, similar to ambient temperature receptors, actively sample environmental CO2 concentrations close to atmospheric levels. Based on recent findings and our data, we hypothesize that Gr-dependent CO2 receptors do not primarily serve as a cue detector to find food sources or avoid danger, instead they function as sensors for preferred environmental conditions.